Floristic analysis of Marmoucha’s plant diversity (Middle Atlas, Morocco) - Nassif, Fatima; Tanji, Abbès (Lazaroa, 2013)
Abstract As part of an ethnobotanical exploration among the Berbers of Marmoucha in the Middle Atlas in Morocco, a floristic analysis is conducted to inventory the existing plants and assess the extent of plant diversity in this area. Located in the eastern part of the Middle Atlas, the Marmoucha is characterized by the presence of various ecosystems ranging from oak and juniperus forests to alfa steppes and altitude cold areas with thorny plants. The fieldwork was conducted over the five years 2008-2012 using surveys and informal techniques. The results show that the number of species recorded in Marmoucha is 514 distributed over 83 families and 323 genera, representing 13.1%, 54% and 30% of species, families and genera at the national level, respectively. With 92 species, the Asteraceae is the richest family, representing 18% of the total reported in the Marmoucha local flora. In second and third places, the two richest families are the Poaceae and the Fabaceae, respectively. From a comparative perspective, the ranking of the eight richest families of the local flora in relation to their position in the national flora reveals a significant match between the positions at local and national levels with slight ranking differences except in the case of the Rosaceae and the Caryophyllaceae. The Asteraceae count 26% of the 50 identified endemic plants in Marmoucha. In Morocco, the Asteraceae holds the first place in terms of species richness and the third in terms of endemic plants with a rate of 24%. With respect to the genera level, local endemism roughly reflects national endemism, with at least one species in four of the five genera rich in endemics (Ononis, Teucrium, Astragalus, and Centaurea). There are 40 species and subspecies considered rare or endangered, distributed in 16 families. With 11 species, the Asteraceae represents 28% of the total of inventoried rare and endangered species. Marmoucha’s floristic heritage is characterized by high diversity and significant importance of endemic, rare, and endangered species. Available information on these species is scarce to inexistent and can be classified among the least studied and least known plants. Therefore, it is imperative to pay further attention to these plants for conservation purposes and if a red list is to be developed in Morocco, it is not inappropriate to begin with these species.